1995
DOI: 10.1021/bp00033a007
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of a Lipase in Ester Synthesis: Effect of Alcohol

Abstract: Ester synthesis by the Mucor miehei lipase has been studied for various alcohol substrates: n‐propanol, n‐butanol, isoamyl alcohol, n‐hexanol, n‐octanol, 2‐ethylhex‐anol, n‐decanol, and lauryl alcohol. The effects of temperature, the nature of the acid, and immobilization of the lipase on its substrate specficity have been elucidated by carrying out esterifications at 29 and 50 °C with lauric and oleic acids and by using both the soluble and immobilized (resin‐adsorbed) forms of the lipase as catalysts. Higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 23 publications
5
33
0
8
Order By: Relevance
“…This is probably due to progressively higher steric hindrance by the methyl groups in the proximity of the hydroxyl group. Results consistent with our work have been observed in previous studies focusing on the effects of the structures of alcohols on ester synthesis catalyzed by lipases [39][40][41]. In general, Fe 3 O 4 -collagen immoblilzed lipases displayed high activity and specificity for butyrate synthesis in an n-hexane medium.…”
Section: Synthesis Of Butyrate By Mnp-col-ilsupporting
confidence: 92%
“…This is probably due to progressively higher steric hindrance by the methyl groups in the proximity of the hydroxyl group. Results consistent with our work have been observed in previous studies focusing on the effects of the structures of alcohols on ester synthesis catalyzed by lipases [39][40][41]. In general, Fe 3 O 4 -collagen immoblilzed lipases displayed high activity and specificity for butyrate synthesis in an n-hexane medium.…”
Section: Synthesis Of Butyrate By Mnp-col-ilsupporting
confidence: 92%
“…Similar observations have been made in other studies on the effect of alcohol chain length on lipase activity. Sawant and co-workers stated a maximum in the initial rate for 1-butanol for both immobilized M. miehei lipase [53] as well as for soluble Lipolase 100 L in a biphasic reaction system [54]. In addition, Delimitsou et al [24] reported the same finding for M. miehei lipase immobilized on HPMC-containing AOT MBG at 25 • C.…”
Section: Effect Of Substrate Chain Lengthmentioning
confidence: 74%
“…Other authors (Abbas et al, 2003;Gandhi et al, 2008;Sun et al, 2009) reported that the methanol molecules are able to bind to the to the active sites of the enzyme, limiting the amount of energy released and consequently preventing the enzyme from changing its conformation to the desired catalytic form. In other words, the enzyme might be partially inhibited in the presence of methanol (Sun et al, 2009).Alcohols have the property of binding to proteins and induce their dehydration, resulting in a drastic loss of enzymatic activity.…”
Section: Effect Of Substrate Concentrationsmentioning
confidence: 99%